GLOBAL MARKETING DECISION DI INDONESIA - Afifah Khairiah Dalimunthe; Siti Julia; Imron Vajirta Nahan Berutu; Suhairi Suhairi (Universitas Labuhanbatu, 2022)
Globalization is a new challenge for companies in implementing marketing strategies. With globalization, companies must compete with world-class companies that have a lot of capital and higher quality products. Currently, Indonesia is the target market for global companies to earn big profits, and Indonesian companies are unable to compete. This study aims to obtain a global marketing strategy for Indonesian companies in the Indonesian market. The research method used is descriptive analysis method. The combination of marketing strategy customization and standard marketing strategy is a global marketing strategy that responds to Indonesian market conditions.